1920
DOI: 10.2105/ajph.10.7.599
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemic of Pneumonic Plague

Abstract: Dr. Kellogg calls on health authorities to wake from their apathy with reference to plague in California, and instead of restrictive measures to adopt an aggressive warfare. He points out that there is real danger to the country and urges adequate appropriations to exterminate the animal disease carriers while this may be done with certainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1950
1950
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…PLAGUE PROTECTION AND F1 VARIANTS 2033 individuals disseminate the disease via aerosol transmission, precipitating its epidemic spread, particularly in crowded settings (31,50). Early efforts to conquer plague derived wholecell vaccines from the pathogen and demonstrated vaccine protection (27).…”
Section: Vol 76 2008mentioning
confidence: 99%
“…PLAGUE PROTECTION AND F1 VARIANTS 2033 individuals disseminate the disease via aerosol transmission, precipitating its epidemic spread, particularly in crowded settings (31,50). Early efforts to conquer plague derived wholecell vaccines from the pathogen and demonstrated vaccine protection (27).…”
Section: Vol 76 2008mentioning
confidence: 99%
“…Expansion events occur in response to conditions that facilitate the dispersal of the infectious agent (32) or to the population dynamics of animal reservoirs (72), the flea vector (5), and human hosts (8,52). Recent epidemiologic surveys have indicated that plague is widespread throughout the wild rodent populations in the southwestern United States, Southeast Asia, Eastern Europe, central and southern Africa, as well as South America, where human populations are highly susceptible (12,16,19).…”
mentioning
confidence: 99%
“…Meyer noted a similar scenario in the Oakland CA outbreak of pneumonic plague in 1919 [8]. Here, the index case was a hunter with bubonic plague and secondary plague pneumonia who infected another man living in the same house.…”
mentioning
confidence: 71%